Using a Logic Model to Enable and Evaluate Long-Term Outcomes of a Mass Casualty Training Program: A Single Center Case Study. (28th June 2022) - Dadario, Nicholas B; Bellido, Simon; Restivo, Andrew; Kulkarni, Miriam; Singh, Maninder; Yoon, Andrew; Shapiro, Jared; Quintero, Frank; Tagami, Tianna; Yang, Christina J; Jafri, Farrukh N
Abstract: Purpose: Global health disasters are on the rise and can occur at any time with little advance warning, necessitating preparation. The authors created a comprehensive evidence-based Emergency Preparedness Training Program focused on long-term retention and sustained learner engagement. Method: A prospective observational study was conducted of a simulation-based mass casualty event training program designed using an outcomes-based logic model. A total of 25 frontline healthcare workers from multiple hospital sites in the New York metropolitan area participated in an 8-hour immersive workshop. Data was collected from assessments, and surveys provided to participants 3 weeks prior to the workshop, immediately following the workshop, and 3 months after completion of the workshop. Results: The mean percentage of total knowledge scores improved across pre-workshop, post-workshop and retention (3 months post-workshop) assessments (53.2% vs. 64.8% vs. 67.6%, P < 0.05). Average comfort scores in the core MCI competencies increased across pre-workshop, post-workshop and retention self-assessments ( P < 0.01). Of the participants assessed at 3 months retention (n = 14, 56%), 50.0% (n = 7) assisted in updating their hospital's emergency operations plan and 50.0% (n = 7) pursued further self-directed learning in disaster preparedness medicine. Conclusions: The use of the logic model provided a transparent framework for the design, implementation, and evaluation of a competency-based EPT program at a single academic center.